Development Of Mobility Application Ajak Mobilitas Based On Sighted Guide Technique For Assisting Individuals With Visual Impairments - Utomo, Utomo; Susanti, Dewi Juwita; Jihadi, Kantata Fatwa; Sari, Purnama (JPK (Jurnal Pendidikan Khusus), 2024)
Providing assistance for individuals with visual impairments can be done by everyone, it's just that in practice it is not in accordance with the right-sighted guide techniques. This research aims to develop the Ajak Mobility application to provide information about various appropriate sighted guide techniques. The research uses the ADDIE development model which consists of stages of Analysis, Design, Development, Application, and Evaluation. The results of the study stated that the Ajak Mobility Application had been developed according to the needs analysis with good and excellent validation results and trial results with very good assessment results. The Ajak mobility application that has gone through a validation and trial process is expected to be an informative application that individuals use to find out how to provide appropriate assistance based on the right-sighted guide techniques to individuals with visual impairments.